2017
DOI: 10.1007/s12029-017-9998-6
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatocellular Carcinoma with Bone Metastases: Incidence, Prognostic Significance, and Management—Single-Center Experience

Abstract: Bone metastases in HCC are very rare and aggressive. Due to its rarity, optimal treatment strategies are not well defined. Early diagnosis is important for optimal therapy and improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…However, the morbidity and mortality of HCC were still high. Widespread metastases remain to be a major challenge for HCC therapy and contributed to the poor prognosis of HCC [2,3]. Therefore, identifying novel regulators related to HCC tumorigenesis, progression and metastasis is still an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…However, the morbidity and mortality of HCC were still high. Widespread metastases remain to be a major challenge for HCC therapy and contributed to the poor prognosis of HCC [2,3]. Therefore, identifying novel regulators related to HCC tumorigenesis, progression and metastasis is still an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…From our 10-year study, only 6% of patients with HCC were found to have spinal metastases with a median survival time of 79 days, which was relatively short compared with that of other common metastatic tumors to the spine such as lung cancer (11.3 months) [12], breast cancer (21.7 months) [13], prostate cancer (58.3 months for hormone naïve and 5 months for hormone refractory [14,15]), thyroid cancer (15.4 months) [16], and cholangiocarcinoma (3 months) [17]. In comparison with other reports on the survival of patients with HCC-derived spinal metastasis [6,18,19], the median survival time after metastasis was also shorter in our study. This could be explained by the lower rate of primary surgical resection and higher rate of palliative treatment and best supportive care in our study.…”
Section: Discussionmentioning
confidence: 88%
“…From our 10year study, only six percent of patients with HCC were found to have spinal metastases with a median survival time of 79 days, which was relatively short compared with that of other common metastatic tumor to the spine such as lung cancer (11.3 months) [12], breast cancer (21.7 months) [13], prostate cancer (58.3 months for hormone naïve and 5 months for hormone refractory [14,15]), thyroid cancer (15.4 months) [16], and cholangiocarcinoma (3 months) [17]. In comparison with other reports on the survival of patients with HCC-derived spinal metastasis [6,18,19], the median survival time after metastasis was also shorter in our study. This could be explained by the lower rate of primary surgical resection and higher rate of palliative treatment and best supportive care in our study.…”
Section: Discussionmentioning
confidence: 89%